THE SALIENCY OF STAKEHOLDERS - Agus Hasan Pura A (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
Stakeholder management is generally viewed as a partnering between the firm and the who the firm considers to its stakeholders and involves